Apicidin biosynthesis is linked to accessory chromosomes in Fusarium poae isolates - Witte, Thomas E.; Harris, Linda J.; Nguyen, Hai D. T.; Hermans, Anne; Johnston, Anne; Sproule, Amanda; Dettman, Jeremy R.; Boddy, Christopher N.; Overy, David P. (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Fusarium head blight is a disease of global concern that reduces crop yields and renders grains unfit for consumption due to mycotoxin contamination. Fusarium poae is frequently associated with cereal crops showing symptoms of Fusarium head blight. While previous studies have shown F. poae isolates produce a range of known mycotoxins, including type A and B trichothecenes, fusarins and beauvericin, genomic analysis suggests that this species may have lineage-specific accessory chromosomes with secondary metabolite biosynthetic gene clusters awaiting description. Methods We examined the biosynthetic potential of 38 F. poae isolates from Eastern Canada using a combination of long-read and short-read genome sequencing and untargeted, high resolution mass spectrometry metabolome analysis of extracts from isolates cultured in multiple media conditions. Results A high-quality assembly of isolate DAOMC 252244 (Fp157) contained four core chromosomes as well as seven additional contigs with traits associated with accessory chromosomes. One of the predicted accessory contigs harbours a functional biosynthetic gene cluster containing homologs of all genes associated with the production of apicidins. Metabolomic and genomic analyses confirm apicidins are produced in 4 of the 38 isolates investigated and genomic PCR screening detected the apicidin synthetase gene APS1 in approximately 7% of Eastern Canadian isolates surveyed. Conclusions Apicidin biosynthesis is linked to isolate-specific putative accessory chromosomes in F. poae. The data produced here are an important resource for furthering our understanding of accessory chromosome evolution and the biosynthetic potential of F. poae.